GBAS: Fundamentals and availability analysis according to σvig - Silva, Weverton Da Costa [UNESP]; Monico, João Francisco Galera [UNESP] (De Gruyter, 2022)
Ground-based augmentation system (GBAS) was developed to guide aircraft precision approach and landing, aiming to replace the instrument landing system (ILS), which is currently used in most airports worldwide. GBAS based on differential positioning with reference stations that provide differential corrections to the aircraft to improve its positioning accuracy and ensure other performance parameters such as integrity, continuity, and availability. However, using GBAS in low latitude regions such as Brazil, the occurrence of ionospheric irregularities can affect global navigation satellite system (GNSS) performance so that it does not meet the requirements for aviation. This article evaluates five vertical ionospheric gradient variability scenarios for a GNSS data set of four reference stations, one station simulating an aircraft with GBAS in a static model based on performance requirements for Category Approach Type - CAT I. The results showed that the increase in the variability of the ionosphere and the geometry of satellites used in positioning could affect the integrity and availability of GBAS. In the scenario of more significant variability of the ionosphere evaluated, there was a loss of 38.4% of the availability of GBAS for the CAT I approach.
Keywords: ionosphere gradient; positions errors; precision approach; protection levels; pseudorange corrections